Assessment of non-neonicotinoid treatments against aphids on sugar beets. (February 2023) - Laurent, Anabelle; Favrot, Armand; Maupas, Fabienne; Royer, Cédric; Makowski, David
Abstract: Aphids can cause significant damage to sugar beet crops . Myzus persicae (Sulzer) (Hempitera: Aphididae), also called green peach aphid, is responsible for transmitting yellows ( i.e ., beet yellows virus, beet mild yellowing virus, beet chlorosis virus, and b eet mosaic virus ) to sugar beet ( Beta vulgaris Linné) that can substantially decrease crop yields and cause significant economic losses. In a context of increasing awareness of environmental health, products containing neonicotinoids were recently banned in several countries, making it necessary to identify new effective means of aphid control. Our study aims to assess the effectiveness of six non-neonicotinoid conventional synthetic insecticides and five biopesticides in reducing the number of aphids on sugar beets. We used data from 35 trials (site-years) managed over five years (from 2018 to 2022) located in France's main sugar beet-producing regions. We fitted a mixed-effect model able to take the variability of treatment effect across site-years into account. The most effective conventional synthetic insecticides were spirotetramat and flonicamid, with a reduction in aphid numbers (compared to the untreated control) of up to 85.6% [95% confidence interval = (80.5; 89.4)] and 79.9% [95% confidence interval = (72.9; 85.2)], respectively, 14 days after their applications at registered rates when combined with oil-based adjuvant. Biopesticides were much less effective, with the best biopesticide ( Lecanicillium muscarium R. Zare & W. Gams Ve6) leading to only 40.7% [95% confidence interval = (16.6; 57.9)] reduction in aphid numbers, 14 days after its application, with great uncertainty due to the limited number of trials available for this product. Our results reveal that the most effective alternative treatments to neonicotinoids could reduce aphid abundance by more than 70% in most cases. Highlights: We assessed non-neonicotinoids insecticides to reduce aphid abundance on sugar beet. Spirotetramat reduced aphid abundance by 85.6% [80.5; 89.4] 14 days after application. Flonicamid reduced aphid abundance by 79.9% [72.9; 85.2] 14 days after application. Biopesticides were less effective and Lecanicillium muscarium was the best one.